Antimalarial Activity of Ugonin J and Ugonin K Isolated from Tunjuk Langit (Helminthostachys zeylanica) - Alvi, Nurul Vadilla; Teruna, Hilwan Yuda; Hendra, Rudi (LPPM Universitas Muhammadiyah Riau, 2025)
Malaria is a life-threatening disease caused by Plasmodium parasites, transmitted by Anopheles mosquitoes, and remains a significant global health issue. This study aimed to identify the antimalarial activity of ugonin J and ugonin K isolated from tunjuk langit (Helminthostachys zeylanica). The in vitro antimalarial assay was conducted using the 3D7 strain of Plasmodium falciparum, which is sensitive to chloroquine, with ugonin J and ugonin K concentrations ranging from 0.01 to 100 µg/mL. The parasitemia percentage was assessed at 48 hours post-treatment, and the percentage inhibition was calculated. The results showed a significant dose-dependent inhibition, with an IC₅₀ value of 0, 041 µg/mL and 0.12 µg/mL, indicating potent antimalarial activity. Ugonin J and ugonin K exhibited effective inhibition of parasitemia at concentrations as low as 1 µg/mL, supporting its potential as a promising antimalarial agent. This study suggests that Helminthostachys zeylanica could be a valuable source of antimalarial compounds